Laporan Keuangan Mudah dengan Si APIK bagi UMKM - Maryati Rahayu; Bida Sari; Nastiti Edi Utami; Jayanti Apri Emarawati (Universitas Persada Indonesia YAI, 2023)
Financial reports are very important when running a business, from micro, small andmedium enterprises (MSMEs) to large scale ones. Financial reports are made so thatentrepreneurs can operate their business properly and can analyze their profits and losses. And itcan also be useful to apply for capital. With the development of technology, making financialreports is easier because there are many applications that can be installed on smart phones. SiAPIK is a financial information recording application that can help MSMEs to do books andrecord their every financial transaction. This community service activity aims to provide financialmanagement and accounting counseling, training on how to download the Si APIK applicationusing the Play Store on an Android cellphone and how to make easy financial reports for OK OCE(Jakpreneur) DKI Jakarta MSMEs. The activity was carried out online using the Zoom media with56 participants. The results of this community service activity are an increase in knowledge aboutthe importance of making financial reports and OK OCE (Jakpreneur) DKI Jakarta SMEs canpractice making financial reports with the Si APIK application using an Android cellphone.Suggestions from this activity are that business actors need to be given further simulations usingcomputers and smart phones in implementing the Si APIK application to make financial reportsfor DKI Jakarta OK OCE (Jakpreneur) MSME actors.